Association Between Protocols of the Sit-to-Stand Test and Lower Limb Muscle Force Output in Patients on Hemodialysis and Subjects Without Chronic Kidney Disease - Lionardo de Paula, Bruno; Pinheiro, Bruno Valle; Segura-Ortí, Eva; Barros, Fabrício Sciammarella; Veras, Priscila Monteiro; Ávila, Kéller Soares; Lucinda, Leda Marília Fonseca; Cavalcanti Garcia, Marco Antonio; Reboredo, Maycon Moura (Journal of renal nutrition, 2023)
To evaluate the association of three protocols of the sit-to-stand (STS) test with muscle force output of knee extension (KE) and knee flexion (KF) in patients on hemodialysis and subjects without chronic kidney disease. This cross-sectional study included a hemodialysis group [n = 60, 59.5 (16.8) years, 55% female] and a control group [n = 60, 43.0 (11.8) years, 50% female]. The assessments were performed in 2 days, and the participants were submitted to three protocols of STS test (5-repetition STS, 10-repetition STS and 30-s STS) or muscle force output of the KE and KF evaluation by handheld dynamometer based on randomization. The hemodialysis group presented reduced muscle force output of the KE and KF, a longer time to perform the 5 STS and 10 STS tests, and a lower number of repetitions in the 30-s STS test. The three STS tests were associated with muscle force output of the KE in the hemodialysis group, in which the 10-repetition STS test showed the best association (R = 0.47; adjusted R = 0.42). However, the only association between the STS test and muscle force output of the KE in the control group was found in the 10-repetition STS test (R = 0.20; adjusted R = 0.13). The three protocols of STS tests were associated with muscle force output of the KE in patients on hemodialysis. However, the 10-repetition STS test was the best protocol to estimate the quadriceps muscle torque in these patients.